Improving the Quality of Student Education: The Effectiveness of the Interactive Comic 'Besok Aja Deh' in Addressing Academic Procrastination - Yusti, Dini Ananda; Zenmira, Kharisma Nanda (Assyfa Journal of Multidisciplinary Education, 2025)
(Background) Time management is a significant challenge among college students, who often face heavy academic, work, and organizational workloads, triggering academic procrastination—the deliberate delay in completing assignments. This behavior directly negatively impacts the quality of learning and the achievement of academic goals, necessitating creative and relevant educational interventions. (Objective) This study aims to test the effectiveness and feasibility of the interactive comic titled "Besok Aja Deh" as a medium to increase time management awareness and reduce academic procrastination among college students. (Method) This development research used a descriptive qualitative and quantitative approach through a simple Research and Development (R&D) method to design the comic media. Product trials were conducted on 54 students at Nahdlatul Ulama University, Pasuruan. (Results) The trial results showed that the comic "Besok Aja Deh" (Tomorrow) achieved a score of 88%, placing it in the "Very Good" category and deemed suitable for use as a medium. Respondents felt the comic improved their understanding of the importance of time management and the consequences of procrastination. (Conclusion) The interactive comic proved effective and suitable for use as a self-education strategy to improve students' self-regulation and time management skills. This media-based intervention significantly contributes to SDG 4: Quality Education by improving students' learning competencies and academic timeliness.